2014
DOI: 10.1002/etc.2675
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of ecological soil‐screening levels for metals to exposure model parameterization and toxicity reference values

Abstract: Ecological soil-screening levels (Eco-SSLs) were developed by the United States Environmental Protection Agency (USEPA) for the purposes of setting conservative soil screening values that can be used to eliminate the need for further ecological assessment for specific analytes at a given site. Ecological soil-screening levels for wildlife represent a simplified dietary exposure model solved in terms of soil concentrations to produce exposure equal to a no-observed-adverse-effect toxicity reference value (TRV).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The European Union's environmental standard for Hg in prey tissue was developed directly from dietary concentrations in toxicity studies and does not account for differences in either ingestion rates or elimination rates. Sample et al found that dose estimation provided no improvement over dietary concentrations in reducing variation in copper toxicity values among species, for either birds or mammals. Although taxonomic similarities in sensitivity are expected, they were evident only when toxicity values were expressed on a dietary concentration basis and not on a dose basis .…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…The European Union's environmental standard for Hg in prey tissue was developed directly from dietary concentrations in toxicity studies and does not account for differences in either ingestion rates or elimination rates. Sample et al found that dose estimation provided no improvement over dietary concentrations in reducing variation in copper toxicity values among species, for either birds or mammals. Although taxonomic similarities in sensitivity are expected, they were evident only when toxicity values were expressed on a dietary concentration basis and not on a dose basis .…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…As noted by previous authors, NOAELs/ LOAELs have shortcomings because of limitations in study design or sample size and lack of attention to the full doseresponse curve or treatment group variability. Furthermore, in certain circumstances, the use of NOAELs/LOAELs may lead to inconsistent, problematic, or inappropriate TRVs to characterize risks (Allard et al 2010;Mayfield and Fairbrother 2013;Mayfield et al 2014;Sample et al 2014aSample et al , 2014b. Thus, performing dose-response analyses, when data are sufficient, is frequently recommended to reduce uncertainty in detailed (postscreening) risk assessments (US Environmental Protection Agency 1997, 1998Allard et al 2010;Landis and Chapman 2011;Mayfield et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A sensitivity analysis of the parameterization of the Eco‐SSL model indicated that although the relative influence of model parameters varied widely among analytes, receptors, and parameters, the TRV consistently exerted the greatest influence on the final value of the Eco‐SSL (Sample, Fairbrother et al ). Beyer and Sample () also evaluated the implications of TRV selection on soil screening levels for 10 metals.…”
Section: Discussionmentioning
confidence: 99%